From Multi-Omics Approaches to Precision Medicine in Amyotrophic Lateral Sclerosis - Morello, Giovanna; Salomone, Salvatore; D’Agata, Velia; Conforti, Francesca Luisa; Cavallaro, Sebastiano (Frontiers in Neuroscience, 2020)
Amyotrophic lateral sclerosis (ALS) is a devastating and fatal neurodegenerative disorder, characterized by upper and lower motor neuron degeneration for which there is no truly effective treatment. The lack of successful treatments can be explained in part by the complex and heterogeneous nature of ALS, with patients displaying widely different patterns of disease manifestation and progression, and molecular analyses suggesting heterogeneity of the underlying biological mechanisms. Thus, stratifying ALS patients into clinically meaningful subgroups can be of great value for advancing the development of targeted therapies and achieving better care for ALS patients. In the last years, the use and integration of high-throughput ‘omics’ approaches have dramatically changed our thinking about ALS, improving our understanding of the complex molecular architecture of ALS, distinguishing distinct patient subtypes and providing a rational foundation for the discovery of biomarkers and new individualized treatments. In this review, we discuss the most significant contributions of omics technologies in unraveling the biological heterogeneity of ALS, highlighting how these approaches are revealing diagnostic, prognostic and therapeutic targets for future personalized interventions.